Continuity and change in Roman religion - Liebeschuetz, J. H. W. G. (John Hugo Wolfgang Gideon) (Clarendon Press ; Oxford University Press, 1979)
This book, first published in 1979 and out of print since 1986, surveys religious attitudes reflected in Latin literature from the late Republic to the time of Constantine. Liebeschuetz focuses on the development of the Roman public religion, particularly the relation between Roman religion and morality."-- publisher description.